Avaliação do perfil farmacocinético do florfenicol em plasma bovino após aplicação intramuscular de duas doses e avaliação da sua eficácia a bactérias sensíveis - Pelissoni, Luís Gustavo Rodrigues [UNESP] (2013)
The florfenicol is an antibiotic used for the treatment of respiratory disease in cattle. Study and understand its pharmacokinetics are important tools for effective control of these diseases and appropriate, thereby minimizing the appearance of resistant bacterial strains. Therefore, this study aimed to determine the pharmacokinetic profile of florfenicol in bovine plasma after intramuscular injection of two doses and evaluate their effectiveness against susceptible bacteria. In the study, we used eight cattle that received two applications of florfenicol and intramuscularly at a dose of 20 mg/kg at intervals of 48 hours. The plasma concentration was determined by high performance liquid chromatography coupled to a mass spectrometer. The minimum inhibitory concentration was performed in a veterinary laboratory following the international standards of the Clinical and Laboratory Standards Institute. Pharmacokinetic parameters were calculated: Cmax = 1.21 ± 0.25 µg/mL, Tmax = 3.43 ± 2.23 h, AUC0-t = 34.16 ± 4.50 h.µg/mL, T½ = 63.46 ± 23.76 h, and Cmax = 1.17 ± 0.20 µg/mL, Tmax = 6.00 ± 0.00 h, AUC0-t = 52.37 ± 5.50 h.µg/mL, T½ = 77.74 ± 43.65 h, respectively for the first and second application. The florfenicol levels in plasma remained above the minimum inhibitory concentration for bacteria: Mannheimia haemolytica (0.75 µg/mL), Pasteurella multocida capsular type A (0.75 µg/mL) and Histophilus sommus (0.30 µg/mL). These results indicate the effectiveness of florfenicol against bacteria that cause respiratory disease of cattle